VD_FINDINFO Faillite / 2013 / 16 vom 5. August 2013 - VD Tribunal cantonal (2013)
CHANGEMENT DE DOMICILE, DOMICILE, COMPÉTENCE RATIONE LOCI, FAILLITE SANS POURSUITE PRÉALABLE | 174 al. 1 LP, 174 al. 2 LP, 46 LP, 53 LP, 59 al. 1 CPC (CH), 59 al. 2 let. b CPC (CH), 60 CPC (CH)